Controlled and protected environment production of blueberries in the Midwest United States - Schwab, Jacob Dillon (Kansas State University, 2020)
For a high value crop such as blueberries, managing growth using both controlled and protected environments may allow for extended or year-round production in the Midwest United States. A series of experiments were conducted in Kansas within a high tunnel and a glass greenhouse to evaluate the potential for containerized blueberry production via soilless substrates and/or with slow-release fertilizers in containers. The first project focused on propagating blueberries in soilless substrates. The second project evaluated plant performance and yield of these plants after they were transplanted into soilless culture. The third project evaluated organic and conventional fertilizers and pH amendments in high tunnel production of blueberries. The half-high Vaccinium corymbosum X angustifolium ‘Northland’ was used in all three projects, and the lowbush Vaccinium angustifolium ‘Brunswick’ was included in some parts of the research. For the propagation project, rooting success was compared between two cultivars, four substrate types, rooting hormone presence or absence, and cuttings of apical or basal stem sections. The ‘Northland’ cultivar had higher rooting success than ‘Brunswick’. Three-to-one peat: perlite was the best substrate with up to 96% rooting success. Cococoir was similarly effective at 88% rooting success. Both shredded rockwool and rockwool cubes resulted in relatively poor rooting of about 50%. Rooting hormone had no effect on rooting success or root ratings, and apical stem sections rooted about 25% better than cuttings from basal stem sections. These propagules were transplanted into one of four soilless production systems: 1:1 peat:perlite drip-irrigated bag culture, rockwool slab drip-irrigated system, cococoir containerized sub-irrigation, or leca clay pebble Dutch bucket system. The Dutch bucket system was removed from the study after the first season due to poor plant performance. Each system type was maintained at one of three volumetric water contents (VWC): 15, 25, or 35%. Due to poor pollination, fruit yield was poor but despite significantly smaller plants, those produced in rockwool yielded more berries than those in peat:perlite, albeit at a lower average weight. Plants grown in peat:perlite accumulated nearly six times the biomass of those produced in either rockwool or coir. In peat: perlite, higher VWC was directly correlated to increased biomass accumulation. High tunnel production of blueberries would have a lower economic barrier to entry than greenhouse production. Blueberries grown with a low or high rate of two fertilizers - one organic and one conventional; and three pH amendments - an organic, conventional, and no application, were compared for yield, growth, and biomass accumulation. Conventional fertilizer yielded healthier plants based on SPAD readings, higher biomass accumulation, and berries with higher soluble solids than the organic fertilizer. The high-rate of both fertilizers also increased growth and overall yield compared to the low-rate. Iron sulfate had no effect on canopy size or fruit yield compared to no pH amendment. Elemental sulfur, when applied at the rate deemed necessary, killed most of the crop and was removed from analyses. This research demonstrates that blueberries can be produced in Kansas using protected and controlled environment production and can be considered by diversified growing operations.
Keywords: Horticulture; Blueberry; High tunnel; Propagation; Vaccinium; Soilless culture